Rebinding of Extracellular Adherence Protein Eap to Staphylococcus aureus Can Occur through a Surface-Bound Neutral Phosphatase - Flock, Margareta (American Society for Microbiology, 2001)
Extracellular adherence protein Eap secreted from Staphylococcus aureus was previously found to enhance the adherence of S. aureus to eukaryotic cells. This enhancement effect is due to the ability of Eap to rebind to S. aureus and to bind to eukaryotic cells and several plasma and matrix proteins. In this study we defined one potential binding target for Eap on the surface of S. aureus, a surface-located neutral phosphatase. This phosphatase lacks an LPXTG region, but around 80% is retained on the cell surface. The soluble phosphatase can form a complex with Eap at a nonrandom molar ratio, and phosphatase activity is retained. The phosphatase can also bind to fibronectin. The cell surface-located portion presumably contributes to adherence of S. aureus to fibronectin.